Devoir et l’évidentialité en français et en roumain - Corinne Rossari; Corina Cojocariu; Claudia Ricci; Adriana Spiridon (Discours)
The French verb devoir has a lexical value (referring to the notion of debt) and several modal values. The analysis proposed will posit that any modal value of devoir codes a form of evidentiality. Devoir indicates that the speaker has motivated his/her utterance by making it depend on a source that coincides with a rule or a fact. Data provided by Romanian and diachronic analysis taking into account the Latin origin of devoir (debere) will support this view. On the one hand they will allow us a better understanding of the way in which the modal values of the French verb came into being. On the other hand, we shall notice that Romanian has a structure named “presumptive” which codes the opposite, i.e. that the information given in the utterance is not dependant on one particular source.